PENGARUH PEMBERIAN BERBAGAI DOSIS (PGPR) DARI AIR CUCIAN BERAS PADA PERTUMBUHAN DAN HASIL TANAMAN PAKCOY (Brassica rapa L.) - Kurnia Ningrum; Umi Barokah (Nusantara Hasana Journal, 2025)
Pakcoy (Brassica Rapa L.) is a type of vegetable that has a lot of nutritional content, including protein, vegetable fat, carbohydrates, fiber, Ca, Mg, Fe, sodium, vitamin A and vitamin C. and the cultivation technique of pakcoy vegetables is very easy to develop and is widely used by those who like and utilize it. In addition, it is also very potential for commercial and has very good prospects. One important technique to increase pakcoy plant production is by providing PGPR rice washing water. The purpose of this study was to determine the effect of providing various doses of Plant Growth Promoting Rhizobacteria (PGPR) from rice washing water on the growth and yield of pakcoy plants, then to determine the best dose of PGPR rice washing water for the growth and yield of pakcoy plants. This study was conducted using 1 factor RAL consisting of 5 levels, namely P0: No treatment (control) P1: PGPR Rice washing water 500 ml/plant P2: PGPR Rice washing water 1000 ml/plant P3: PGPR Rice washing water 1500 ml/plant P4: PGPR Rice washing water 2000 ml/plant, by conducting further tests using DMRT on significantly different results. The results of the analysis had a significant effect on the observation variables of plant height Week 1, number of leaves Week 1, number of leaves Week 2, crown width Week 4, stem diameter Week 2,3,4 and had no significant effect on plant height 2,3,4,5 and crown width. Then it had a very significant effect on the number of leaves Week 5, stem diameter Week 1 and stem diameter Week 5.